Aspects of Serological Diagnostics of Listeriosis (Literature Review) - Natalya M. Khaptanova; Nina M. Аndreevskaya; Svetlana V. Lukyanova; Zhanna A. Konovalova; Natalya G. Gefan; Аleksandr S. Ostyak; Elena G. Tokmakova (Acta Biomedica Scientifica, 2019)
The review presents data on the antigenic structure and the current classification of epidemically significant serovariants of Listeria. Description of species-specific properties of serovariants of Listeria, which may be common for two or more species, and common antigens with staphylococci and typhoid and paratyphoid bacteria, are given. It has been shown that only the antigenic scheme of Listeria monocytogenes is of practical interest for medical microbiology. Importance of serotyping in the epidemiological analysis to determine the source of infections and ways of its spreading has been determined. Differences in the designation of serovariants in the diagnosis of listeriosis in medical practice are observed. High level of adaptive properties of Listeria, its ability to reproduce in an abiotic environment, including food, susceptibility of immunodeficient individuals, prevalence of food pathway of infection pose a significant danger of increased sickness rate with listeriosis. Serological diagnostics of Listeria has not been developed in detail, and the existing serological methods are aimed at identifying specific antibodies to listeria. Advantages of the serological method include: quick results and the possibility to study any biological material. Currently available serological methods have a number of disadvantages: low reliability of results and low specificity of the study. The most promising method for identification of a serological group of cultures, according to the world classification, is the multiplex PCR method, based on the correlation between the serogroup of an isolate and the presence of specific open reading frames in its genome.